PTH-036 Effectiveness of endoscopic retrograde cholangiopancreatography for palliative biliary drainage in patients with inoperable hilar cholangiocarcinoma and its impact on survival. (22nd June 2015) - Aujla, UI; Ladep, N; Lee, HL; Noorullah, O; Dwyer, L; Stern, N; Hood, S; Sturgess, R
Abstract : Introduction: Cholangiocarcinoma (CCA) has a poor prognosis and is often unresectable at presentation. Palliative stenting is the goal in unresectable disease followed by chemotherapy in suitable patients. In our unit endoscopic retrograde cholangiopancreatography (ERCP) is preferred initial approach for biliary drainage and tissue acquisition. To optimise drainage in some patients this is combined with percutaneous bile duct drainage (PTC). Meticulous pre-procedural work up is required to select suitable sector for drainage and to minimise subsequent cholangitis in complex hilar lesions. The aim of this study was to determine the effectiveness of ERCP in unresectable hilar CCA and survival advantage related to bile duct drainage. Method: A single large volume tertiary referral centre study looking at ERCP records of patients with hilar CCA using a prospectively collected procedural database together with an electronic hospital clinical record over a period of six years from Jan 2009 to Dec 2014. Results: ERCP was performed for palliative biliary stenting in 207 patients with hilar CCA (99 males and 108 females) with median age of 73 years (range 34–95 y). Median number of ERCPs performed was 2 (range 1–12). 190 (92%) patients had self-expandable metal stents (16 covered and 174 uncovered) for biliary drainage while remaining 17(8%) had plastic stents. Median serum bilirubin pre and post-stenting was 238 (95% CI: 225–264) umol/l and 39 (95% CI: 31–49) umol/l, respectively (p < 0.001). 154 (74%) patients had unilateral stenting for biliary drainage, while 53(26%) patients required bilateral stenting for complex strictures. 45 (22%) patients with hilar CCA required additional PTC for optimal drainage. Median survival of patients with hilar CCA who had bilateral stents was 8 (95% CI: 4–13) months, while those who had unilateral stenting was 5 (95% CI: 4–8) months (p = 0.22). 55 (36%) patients with unilateral stenting and 18(34%) with bilateral stenting had repeat procedures due to episodes of stent blockage and cholangitis. There was no direct procedure related mortality. Conclusion: Endoscopic bile duct drainage provides effective and rapid decompression in patients with advanced hilar CCA. We aim to drain more than 50% of biliary tree, which was achieved with either unilateral or bilateral stenting. Choice of unilateral or bilateral stenting is dependent on pathological biliary tree anatomy. In our experience there was no statistically significant survival advantage among patients with unilateral and bilateral stenting of complex hilar lesions. Disclosure of interest: None Declared.